Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsaelm.8b00047
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability Analysis of Ternary Alkaline-Earth Hexaborides: Insights from DFT Calculations

Abstract: We present a phase stability analysis of ternary mixtures of alkaline-earth hexaborides using insights from DFT calculations to determine the effect of homogeneity on properties including stability and domain formation. We find that linear mixing rules and Vegard’s law type, describe very well octahedral volumes, inter and intraoctahedral bond lengths, lattice constants, bulk moduli, cation–facial distances for the mixtures of M x 1M1–x 2B6, where M k can be Ca, Ba, or Sr, and composition (x) ranges from 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Previous study by Cohen [51] revealed the power law dependence of bond length (d) with K for covalent crystal as K ∝ d −3.5 and for ionic crystal as K ∝ d −3 . In both cases it is evident that K will decrease with the increase in d [52,53]. In case of Cu 2 Se (Cu-Se bond length 2.56 Å), the size of Cu atom (140 pm) is much smaller than Sn atom (225 pm) in SnSe (Sn-Se bond length 2.83 and 2.79 Å) which eventually leads the formation of shorter bonds in Cu 2 Se and making K larger.…”
Section: Marmentioning
confidence: 96%
“…Previous study by Cohen [51] revealed the power law dependence of bond length (d) with K for covalent crystal as K ∝ d −3.5 and for ionic crystal as K ∝ d −3 . In both cases it is evident that K will decrease with the increase in d [52,53]. In case of Cu 2 Se (Cu-Se bond length 2.56 Å), the size of Cu atom (140 pm) is much smaller than Sn atom (225 pm) in SnSe (Sn-Se bond length 2.83 and 2.79 Å) which eventually leads the formation of shorter bonds in Cu 2 Se and making K larger.…”
Section: Marmentioning
confidence: 96%
“…Strain effects have also been explored as parameters for morphological modification of copper and nickel particles, and doping has been applied for obtaining nanorods of magnesium . In addition, modeling and experimental techniques have been applied for exploring the behavior of borides of cubic and other morphologies. Moreover, experimental efforts have investigated shape change in cubic carbides as a function of carbon stoichiometry, which influences the relative growth rate of the dominant {111} and {100} facets. …”
Section: Introductionmentioning
confidence: 99%